Video Pembelajaran Berbasis Kearifan Lokal Pada Mata Pelajaran Bahasa Osing Siswa Kelas VI - Teresiya, Henny Wanda; Alexander Hamonangan Simamora; I Made Tegeh (Journal for Lesson and Learning Studies, 2023)
Learning in elementary schools is still teacher-centred and uses conventional media to make students less active, decreasing their interest and learning outcomes. This research aims to develop learning videos based on local wisdom for class VI SD. This type of research is the ADDIE development model. The subjects in this study were learning media content experts, design experts, learning media experts, and 11 grade VI elementary school students. Data collection in the study was carried out using the questionnaire and observation methods, with research instruments in the form of expert test questionnaires and student trials. The data obtained in the study were then analyzed using qualitative and quantitative data analysis techniques. The results of the data analysis showed that the results of the learning content expert test obtained a score of 94%. The learning design expert test obtained a score of 88.00%. The media expert test obtained a score of 92% learning. Individual trials obtained a score of 93.33%. The small group trial obtained a score of 92.5%, which was very well-qualified in all percentages. Based on these results, it can be concluded that learning video media based on local wisdom for class VI is very qualified, so it is feasible to develop and teach elementary school students, especially in Osing language learning material.